ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI TUNGGAKAN PAJAK BUMI DAN BANGUNAN DI KELURAHAN SOLOR - Rosita Rosita; Meyulinda Aviana Elim; Rosdiana Mata (JAKA - Jurnal Jurusan Akuntasi, 2020)
Land and building tax is one type of tax in Indonesia that contributes to state financial revenue for financing government administrators and national development. The researcher aims to find out what factors influence land and building tax levels. Several approaches are needed using data collection techniques through direct interviews and direct observation or observation of the research location. The data analysis techniques used in this study were: statistical analysis and linear regression analysis. The variables studied: X1 (factor of consciousness), X2 (factor negligence), X3 (ability factor), Y (Land and building tax arrears). The hypothesis 1 testing results indicate that the awareness variable partially has a negative and significant effect on the land and building tax arrears variable. The hypothesis 2 testing results indicate that the taxpayer negligence variable partially has a positive and significant effect on the land and building tax arrears variable. The hypothesis 3 testers show that the ability variable partially has a negative and significant effect on the land and building tax arrears variable. The results of hypothesis testing 4 indicate that the variables of taxpayer awareness, taxpayer negligence and the ability of taxpayers simultaneously have a significant effect on land and building tax arrears.